A Highly Selective and Strong Anti-Interference Host-Guest Complex as Fluorescent Probe for Detection of Amantadine by Indicator Displacement Assay - Linzhao Zhu (Molecules, 2018)
Amantadine (AMA) and its derivatives are illicit veterinary drugs that are hard to detect at very low concentrations. Developing a fast, simple and highly sensitive method for the detection of AMA is highly in demand. Here, we designed an anthracyclic compound (ABAM) that binds to a cucurbit[7]uril (CB[7]) host with a high association constant of up to 8.7 × 108 M−1. The host-guest complex was then used as a fluorescent probe for the detection of AMA. Competition by AMA for occupying the cavity of CB[7] allows ABAM to release from the CB[7]-ABAM complex, causing significant fluorescence quenching of ABAM (indicator displacement assay, IDA). The linear range of the method is from 0.000188 to 0.375 μg/mL, and the detection limit can be as low as 6.5 × 10−5 μg/mL (0.35 nM). Most importantly, due to the high binding affinity between CB[7] and ABAM, this fluorescence host-guest system shows great anti-interference capacity. Thus, we are able to accurately determine the concentration of AMA in various samples, including pharmaceutical formulations.